High body mass index is a predictor of left ventricular reverse remodelling in heart failure with reduced ejection fraction. (27th July 2017) - Cescau, Arthur; Van Aelst, Lucas N.L.; Baudet, Mathilde; Cohen Solal, Alain; Logeart, Damien
Abstract: Aims: Structural and functional left ventricular alterations can occur in heart failure (HF), referred to as left ventricular reverse remodelling (LVRR). This study aimed to define novel predictors of LVRR besides well‐known effects of medical and device therapy. Methods and results: From echographic database, we included 295 patients with both left ventricular ejection fraction (LVEF) ≤45% and indexed left ventricular end‐diastolic diameter ≥33 mm/m 2 and who had at least two echocardiographic exams with a delay between 3 and 12 months. LVRR was defined as the combination of (i) normalization of LVEF (LVEF ≥50%) or increase in LVEF ≥10% and (ii) a decrease in indexed left ventricular end‐diastolic diameter ≥10%. Clinical follow‐up was also obtained. LVRR occurred in 53 (18%) patients. Patients in the LVRR group were more likely to present with de novo HF (75% vs. 42%), had lower LVEF and left ventricular end‐diastolic volumes at index examination, yet a higher body mass index (BMI) than non‐LVRR patients. Obesity was observed in 25% of LVRR patients vs. 14% in others. In multivariate analyses, BMI (per each 1 kg/m 2 increase) emerged as a predictor of LVRR: odds ratio 1.10 (95% confidence interval 1.02–1.19) after adjustment to other predictors of LVRR. During a mean follow‐up of 37 months, 32% of patients had a major adverse cardiac event; de novo HF, age, and LVEF were associated with major adverse cardiac event. Conclusions: We identified significant relationship between high BMI and LVRR. This intriguing novel finding deserves further study.